2003
DOI: 10.1080/00365520310006432
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy‐negative reflux disease: what is the value of a proton‐pump inhibitor test in everyday clinical practice?

Abstract: Application of a diagnostic PPI test in clinical practice gave a high sensitivity and unusually low specificity compared to placebo-controlled studies, indicating that a test of this nature should be used with caution in everyday practice. Most patients with endoscopy-negative GORD will be diagnosed clinically. A positive test with PPI strengthens the diagnosis but has insufficient specificity to be an objective criterion alone. pH-metry should be unnecessary for the diagnosis of ENGORD in patients with typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…After full-text review, studies unrelated to diagnostic tests for GERD ( n = 23), studies not in English/Chinese language ( n = 2), and studies not eligible for enrollment ( n = 3) were excluded. Altogether, a total of 40 published studies meeting the predetermined inclusion criteria were identified 1352 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…After full-text review, studies unrelated to diagnostic tests for GERD ( n = 23), studies not in English/Chinese language ( n = 2), and studies not eligible for enrollment ( n = 3) were excluded. Altogether, a total of 40 published studies meeting the predetermined inclusion criteria were identified 1352 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of this observation, the use of a single sodium alginate dose as a diagnostic tool in patients with symptoms suggestive of GOR seems promising, although this requires further investigation before being formally proposed. Indeed, since the currently used standard short-term treatment with proton pump inhibitors as a test for GOR (PPI test) requires a 1-to 2-week period of high-dose treatment and has a sensitivity of approximately 80%, with a poor specificity [15,16], use of a single dose of sodium alginate might exhibit a higher sensitivity, better compliance derived from single dosing, and rapid interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…La prueba del IBP tiene igual fundamento, pero presenta algunas diferencias debidas a su objetivo diagnóstico 12 . Se ha experimentado con todos los IBP disponibles administrados habitualmente en una dosis mayor de la convencional (por lo común doble) y durante un plazo más corto (5-15 días) [13][14][15][16][17][18][19][20] . Se considera positiva, esto es, diagnóstica de ERGE, cuando se constata la remisión o la mejoría significativa de los síntomas (descenso del 50-75% del índice sintomático).…”
Section: Discussionunclassified